PENGARUH RELATIONSHIP MARKETING DAN LOYALITAS PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MIXUE MAKASSAR - Reni Anastasia; Noviantry Ruruk; Amir Jaya; Johannes Baptista Halik; Jerliyen Pramita Londong (Yos Soedarso Economic Journal (YEJ), 2023)
This research aims to see the influence between relationship marketing and customer loyalty on Mixue consumer purchasing decisions in the city of Makassar. This research took a sample of 50 people using the convenience sampling method from Mixue consumers in the city of Makassar. The data was then analyzed using statistical data analysis techniques using the SmartPLS version 4 application. From the research results it was found that Relationship marketing did not affect the purchasing decisions of Mixue consumers in the city of Makassar. Service quality has a positive and significant effect on Mixue consumer purchasing decisions in the city of Makassar. Based on these results, the author suggests that Mixue be able to handle consumer complaints better and create customer loyalty so that they do not lose out in today's increasingly fierce competition.